في القرآن عند الرازيُ نْ وُ كَ يَ فـْ نُتفسير آية ك - Muhammad Badrun Syahir; Faridah Aryani (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
The incorrect understanding of the verse Kun Fayaku>nu is closely related to theological issues. Al-Razi a mufassir who prioritizes ilm kala>m, uses the method of interpretation by mentioning the thoughts of Mu’tazilah, Karamiyah, and other deviant groups, then criticizing them based on the school of ahlu al-sunnah wa al-jama>’ah. He interpreted where the purpose of the verse is the speed of the breakdown of God’s power and His will in creating creatures or carrying out something new without anyone being able to oppose Him. Al-Razi interpreted that the command to what did not yet exist was not true, because what did not yet exist was invalid as something. While Allah’s words are qadi>m, while Allah’s chanting with the word Kun is muh}dats, then the original will is passed on to the will which depends on His commands with Kun’s words.